Crime and Punishment: Prigoshin’s Mutiny and Putin’s Revenge in Ukrainian and Russian Cartoons and Memes - Orest Semotiuk (Cognitive Studies | Études cognitives, 2024)
The paper deals with the discursive dimension of two episodes of the Russo–Ukrainian war: The rebellion of Yevgeny Prigoshin (founder of the Wagner private military company) on 23 June 2023, and his death in an airplane crash on 23 August 2023. This dimension is implemented in Ukrainian and Russian political humor. Political satire, as a form of Humorous Media Political Discourse, can be described by its target, focus and setting. Political cartoons and memes, as genres of Humorous Media Political Discourse, can be defined by their goals, frame of reference and means. These corresponding parameters (goal–target, frame of reference–focus, means–setting), as well as the correlation between the discursive dimension and social context, provide the analytical framework for the paper. The methodology is based on the discourse and multimodality theories. Special attention is paid to the interaction of verbal and nonverbal elements in cartoons and memes, as well to similarities and differences in Ukrainian and Russian cartoons and memes depicting Yevgeny Prigoshin’s rebellion and his death.